2005
DOI: 10.1001/archpedi.159.4.320
|View full text |Cite
|
Sign up to set email alerts
|

Oxycodone vs Placebo in Children With Undifferentiated Abdominal Pain

Abstract: Early administration of buccal oxycodone provides a significant pain relief to children with acute abdominal pain, without adversely altering the clinical signs or obscuring the surgical diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 16 publications
(37 reference statements)
0
20
0
Order By: Relevance
“…In the study by Green et al, 36 this estimate was not available, and the final (postintervention) score was used in the meta-analysis. Kokki et al 37 reported a summed and maximal pain intensity difference. The latter was incorporated into the meta-analysis because we believed it most closely parallels measures of pain in other studies.…”
Section: Summary Measures and Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study by Green et al, 36 this estimate was not available, and the final (postintervention) score was used in the meta-analysis. Kokki et al 37 reported a summed and maximal pain intensity difference. The latter was incorporated into the meta-analysis because we believed it most closely parallels measures of pain in other studies.…”
Section: Summary Measures and Synthesis Of Resultsmentioning
confidence: 99%
“…The latter was incorporated into the meta-analysis because we believed it most closely parallels measures of pain in other studies. 37 Kim et al 38 reported differences in pain scores as median and interquartile range. Efforts to obtain the original data for parametric analyses were unsuccessful and the results were not included in the meta-analyses.…”
Section: Summary Measures and Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Providers were initially resistant to enrolling patients in the study because of the fear of providing analgesia to these patients, although this is unsupported by much of the published literature to date. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Assembly bias may have been generated by non-consecutive patient enrollment. Patients collected by convenience or because the physician suggested enrollment in a study may be a subset of the population unless all patients are contributed to the study.…”
Section: Commentarymentioning
confidence: 99%
“…4 In the past decade there has been growing evidence demonstrating that opioid analgesia is safe and appropriate in ED patients with undifferentiated acute abdominal pain. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The literature has documented how pain is an inadequately treated symptom in the ED. This may be related, in part, to our current emergency medicine culture.…”
Section: Introductionmentioning
confidence: 99%